Association of Type 2 Deiodinase Thr92Ala Polymorphism with Pediatric Obesity in Japanese Children: A Case-Control Study - Takeshi Ota; Jun Mori; Yasuhiro Kawabe; Hidechika Morimoto; Shota Fukuhara; Kazuki Kodo; Satoru Sugimoto; Kitaro Kosaka; Hisakazu Nakajima; Hajime Hosoi (MDPI AG, 2022)
Genetic factors play critical roles in the onset and progression of obesity. Brown adipose tissue (BAT) activity is also critical for adiposity. The objective of this study was to evaluate the prevalence and effects of BAT gene polymorphisms in pediatric obesity. This case-control study included 270 non-obese and 86 obese children. All participants underwent genotyping for type 2 deiodinase (DIO2) Thr92Ala (rs225014). The prevalence of the homozygous Ala/Ala allele of the DIO2 gene in the obese group was 15.1% versus 6.3% in the non-obese group, resulting in an odds ratio (OR) of 3.393 (p = 0.003). The results of this study indicate that the homozygous Ala/Ala allele of the DIO2 gene is associated with an increased risk of pediatric obesity and suggest that pediatric obesity might be suitable for assessing the association with gene polymorphisms related to BAT, especially DIO2 Thr92Ala.